MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU PADA SMP NEGERI 6 BANDA ACEH - Linda Marlina; Cut Zahri Harun; Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
The objective of this research was to find out the principal’s management behavior in improving the teachers’ pedagogical competence at State Junior High School 6 of Banda Aceh.  This qualitative research was conducted by means of a descriptive method.  The results showed that (1) the program was arranged at the beginning of each academic year by creating a TPS in accordance with the results of discussions and meetings with several related parties. The program arranged in the RKAS consisted of workshop and training in writing lesson plans, making exam content outlines, preparing teaching instruments, conducting classroom action research, supervising classes, and doing IHT and school self-evaluation. In addition, (2) the implementation of the program was started with dividing tasks and authorities, conducting meetings, sharing information, and briefing. Moreover, a reward was given to every teacher with good performance while each teacher with poor performance received punishment. However, (3) there was no instrument used as the guideline in the evaluation of each workshop, classroom action research, and IHT. The results of evaluation were documented and presented to each teacher or a group of teachers in order to be considered in the following year program. Lastly, (4) lack of workshop and training, time and motivation to read relevant books or journals.Keywords: management, behavior of principal, pedagogical competence of teacher